A house of one's own : the moral economy of post-disaster aid in El Salvador - Sliwinski, Alicia (McGill-Queen's University Press, 2018)
What happens to people after an earthquake destroys their homes? What is daily life like under a humanitarian regime? Is aid a gift or is it a form of power? A House of One's Own explores these enduring questions as they unfold in a Salvadoran town in the aftermath of the 2001 earthquakes. In a lively, intimate account of the social complexities that arise in post-disaster settings, Alicia Sliwinski recounts the trajectories of fifty families who received different forms of humanitarian aid, from emergency assistance to housing reconstruction. Drawing on seminal anthropological theories about gift giving and moral economy, the author thoughtfully discusses the complications and challenges of humanitarian action that aims to rebuild communities through participation. At the crossroads of disaster studies and the anthropology of humanitarianism, the book's insights speak to timely and recurring issues that relocated populations face in regimented and morally charged resettlement initiatives. A richly textured, analytically nuanced ethnography, A House of One's Own is a perceptive firsthand account of what happens on the ground in a post-disaster setting.